Equilibrium morphologies for Cl-roughened Si(100) at 700–750 K: Dependence on Cl concentration - Xu, G. J. (2003)
Adsorbed halogen atoms on Si(100)-(2×1) can induce roughening at temperatures where material removal (etching) is minimal. Variable temperature scanning tunneling microscopy was used to follow roughening at 700–750 K for surfaces with 0.1–0.99 ML of Cl. Dimer vacancies and Si adatoms were observed at short times, and at longer times the progression toward a state of dynamic equilibrium was traced. Once dynamic equilibrium was reached, the appearance of individual pits and regrowth islands changed but their densities and mean sizes did not. The results show that the roughness depends nonlinearly on Cl coverage with surfaces having 0.3 ML being nearly ten times rougher than those with 0.1 ML. The importance of Cl-free dimers is stressed, and the role of Cl as an impediment for vacancy and adatom diffusion is demonstrated. Roughening is attributed mainly to adsorbate-adsorbate repulsive interactions.